Role of Nurse in Public Health According to Indonesian Law - Widjaja, Gunawan; Sijabat, Hotmaria Hertawaty (International Journal of Psychosocial Rehabilitation, 2020)
The Law No.38 Year 2014 regarding Nurse (the Nursing Law) provides the possibility for nurses to have their own private practice. Based on Article 30 the Nursing Law, nurses may also provide nursing care in public health. The aim of this research is to define and elaborate the role of nurses in public health conducted in their own private practice according to the nursing law and other related laws applicable in Indonesia. Data used in this research were secondary data, obtained through internet search using google machine. The collected data were analyzed using content analysis to reduce only to relevant data. The relevant data were then analyzed using qualitative method with normative and comparative approach. Result shows that based on understand Law No.36 Year 2009 regarding Health (the Health Law) and Law No.36 Year 2014 regarding Healthcare Givers (the Healthcare Givers Law), each health profession has its own competencies. Therefore, nurses in providing nursing care in public health, nurses are required to obtain public health competencies, besides all the requirements that must be complied in accordance with the Nursing Law. In practice, nurses can play many roles in public health care, in conditions that she/ he shall not conducts activities in public health which do not belong to their competencies. According to Indonesian laws, the role of nurses in public health are somehow limited because of the competencies’ issues.